Dream Country - Gibney, Shannon (New York, NY : Dutton, 2018)
"Spanning two centuries and two continents, [this] is the story of five generations of young people caught in a spiral of death and exile between Liberia and the United States"--
Includes filmography and bibliographical references (pages 342-343).
Keywords: Families -- Juvenile fiction -- Liberia; Families -- Juvenile fiction -- Minnesota; Slavery -- Juvenile fiction; Refugees -- Juvenile fiction; Liberian Americans -- Juvenile fiction; African Americans -- Juvenile fiction; Americans -- Juvenile fiction -- Liberia; Family life -- Fiction -- Liberia; Family life -- Fiction -- Minnesota; Slavery -- Fiction; Refugees -- Fiction; Liberian Americans -- Fiction; African Americans -- Fiction; Americans -- Fiction -- Liberia; JUVENILE FICTION / People & Places / United States / African American; JUVENILE FICTION / Historical / Africa; JUVENILE FICTION / Social Issues / Prejudice & Racism; Liberia -- Juvenile fiction -- History -- To 1847; Liberia -- Juvenile fiction -- History -- 1847-1944; Liberia -- Juvenile fiction -- History -- 1980-; Minneapolis (Minn.) -- Juvenile fiction; Liberia -- Fiction -- History -- To 1847; Liberia -- Fiction -- History -- 1847-1944; Liberia -- Fiction -- History -- 1980-; Minneapolis (Minn.) -- Fiction